2000
DOI: 10.1046/j.1460-9568.2000.00259.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of nicotinic acetylcholine receptors induces long‐term potentiation in vivo in the intact mouse dentate gyrus

Abstract: The present study was conducted to clarify the role of nicotinic ACh receptors (nAChRs) on long-term potentiation (LTP) in vivo in the intact mouse dentate gyrus using extracellular recording techniques. Intraperitoneal application of nicotine at a dose of 3.0 mg/kg but not 0.03 or 0.3 mg/kg produced a gradually developing, long-lasting increase for 120 min similar to tetanic LTP. Nicotine at a dose of 9. 0 mg/kg caused a temporary increase followed by depression. The long-lasting potentiation induced by nicot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
106
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 138 publications
(112 citation statements)
references
References 34 publications
6
106
0
Order By: Relevance
“…Indeed, activation of a 7 nAChRs facilitates LTP induction in the rat hippocampus (21) and produces LTP induction in the rat midbrain (22). We also showed that intraperitoneal application of choline, a selective a7 nAChR agonist, induced smaller LTPn in the mouse dentate gyrus (7). However, there is no evidence about the involvement of a 4b2 nAChRs, which are the most abundant subtype of nAChRs in the brain, in LTP.…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…Indeed, activation of a 7 nAChRs facilitates LTP induction in the rat hippocampus (21) and produces LTP induction in the rat midbrain (22). We also showed that intraperitoneal application of choline, a selective a7 nAChR agonist, induced smaller LTPn in the mouse dentate gyrus (7). However, there is no evidence about the involvement of a 4b2 nAChRs, which are the most abundant subtype of nAChRs in the brain, in LTP.…”
Section: Introductionmentioning
confidence: 66%
“…We used mecamylamine at a dose of 0.5 mg / kg as a non-selective nAChRs antagonist as shown in our previous report (7). Mecamylamine and epibatidine were applied to examine how the a 4b2 nAChRs are involved in LTPn in vivo in the intact mouse dentate gyrus.…”
Section: Epibatidine-induced Ltpn Is Inhibited By Pre-treatment Of Mementioning
confidence: 99%
See 1 more Smart Citation
“…(Monmaur, Collet, Puma, Frankel-Kohn, & Sharif, 1997;Yoder & Pang, 2005). Previous studies have shown that acetylcholine during REM sleep following a learning task plays an important role in memory consolidation (Matsuyama, Matsumoto, Enomoto, & Nishizaki, 2000;Smith, Tenn, & Annett, 1991). In addition, a more recent study by Davis et al (2006) indicated that RSD severely hampers cytoskeletal reorganization in the hippocampus, a process that is essential for synaptic plasticity and memory consolidation.…”
Section: Discussionmentioning
confidence: 99%
“…Either application of nicotine in brain slices or subcutaneous injection of nicotine, in vivo, enhances LTP in dentate gyrus (Sawada et al 1994;Curran and Connor 2003;Welsby et al 2006Welsby et al , 2009. Acute nicotine treatment prevents sleep deprivation-induced impairment of LTP in the DG (Aleisa et al 2011) and administration of a highdose of nicotine causes synaptic potentiation in the DG, without pairing of tetanic stimulation (Matsuyama et al 2000;Tang and Dani 2009). These studies in the DG have, however, focused on the effects of nicotine alone.…”
mentioning
confidence: 99%